Women Empowerment through Mobile Phone: Case Study of Bangladesh (Global Journal of Human-Social Science, 2021)
Telecommunication particularly Mobile technology is one of the most powerful tools worldwide Mobile phones play a foremost part in development programs around the world The diffusion of mobile phones performs a great role in development programs along with overall empowerment in developing countries Telecommunication is most powerful to combat poverty and give the people a chance to change their fate their economy their society and to empower themselves to change the world especially for women Large sections of women in Bangladesh are living in rural areas The majority of them are still tradition-bound and are in a disadvantageous position Because of inequality in women s access to and participation in all communication systems and their lack of sufficient mobility to promote their contribution to society women are deprived in every aspect of life Mobility is a very important factor for women s empowerment The Mobile phone revealed the opportunities and freedom for women to make their own choices improve their social network change their attitudes and change their life
Keywords: empowerment; women empowerment; telecommunication; mobile phone; sustainable development